Ecobrick Innovation For Plastic Waste Reduction And Community Environmental Awareness In Sijunjung - Arininisaulkhaira_17; Dony Novaliendry; Divia Tri Ananda; Helma Wadria Putri; Helmi Wadria Putri; Mutia Ulfah; Nursipa Amanda; Khafila Demara; Parbagian Tambunan; Qodrialfarisi Tambunan (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study addresses plastic waste management challenges in Sijunjung Regency by introducing ecobrick innovation to enhance environmental sustainability and community awareness. Method: Employing a community service approach, the research utilized literature review and field observation methods. Data were collected through documentation and direct observation of ecobrick production in Jorong Taruko Nagari Tanjung, then analyzed descriptively. Practical Applications: Ecobricks transform non-organic plastic waste into functional garden elements, providing communities with a creative, low-cost waste management solution that improves environmental aesthetics, reduces pollution, and strengthens collective environmental stewardship through participatory engagement. Conclusion: The initiative significantly shifted community mindsets toward sustainable waste practices, demonstrating ecobrick as an effective, innovative strategy for mitigating plastic pollution while fostering cleaner, healthier, and more sustainable living environments through empowered local action.